DEVELOPMENT OF NICKEL-BASED CATALYST WITH ADDITION OF ALKALINE EARTH METAL PROMOTER FOR DRY REFORMING OF METHANE - Reyhana, Wulan
Natural gas reserves in the Natuna Islands are one of the largest natural gas reserves in Indonesia with an exploitable gas capacity of up to 46 TCF. However, natural gas in Natuna Islands has a very high CO2 content. Therefore, a technology to increase its economic value by converting the natural gas into liquid fuel is needed. Dry Reforming of Methane (DRM) is a technology that utilizes CO2 for the reforming process to produce a syngas mixture of CO and H2 which is an important precursor for valuable chemicals and liquid fuel productions. The main challenge associated with DRM is to find a catalyst that has a high catalytic activity and good thermal stability to prevent catalyst deactivation due to the high temperature of the process. One of the catalysts that has high catalytic activity and economically feasible is Ni-based catalyst. However, this catalyst needs to be subsequently modified to enhance the catalytic activity and thermal stability. In this research, the development of Ni catalyst was carried through by adding cerium and zirconium support to Ni catalyst (10%Ni/CeZrO2). The development of the catalyst also done by adding 1% of basic promotor to the 10%Ni/CeZrO2 catalyst to enhance the basicity of the catalyst so that the deactivation process could be delayed. After the addition of promotor, synthesized catalyst would be characterized, and the activity and stability of the catalyst would be evaluated on 700 ?C, flow rate of 60 mL/min, and atmospheric pressure. The amount of catalyst that is obtained at the end of the experiment weighed 60 mg. The result of the catalyst performance test conducted at temperature of 700 °C, atmospheric pressure, and WHSV 60,000 mL·g-1·h-1 showed that the 10%NiO- 1%Mg/CeZrO2 catalyst had the highest activity with conversions of CH4 and CO2 at 78% and 64%, yields of H2 and CO products at 56% and 41%, and H2/CO ratio around 1.53 compared to other basic promoters. The results of TGA analysis showed that adding basic promoters to 10%Ni/CeZrO2 catalyst improve the thermal stability proven by 10%Ni- 1%Na/CeZrO2 catalyst that has the least weight loss at 10% weight loss.